Nilai Ekonomi Kebun Binatang Surabaya denga Pendekatan Travel Cost Method - Shilvina Widi Irsanti; Tri Haryanto; Deni Kusumawardani (MediaTrend, 2020)
Surabaya as big cities have an appeal that very large for their citizens and residents from other cities which comes as newcomers to work as well as settled or seek education. One of them is the attractiveness of tourism in the number of visitors highest in Surabaya was a zoo Surabaya. The frequency of visits the zoo Surabaya influenced by age variable, married status, the distance, education, and the costs to transport the while variable gender and income has no significant impact on the frequency of visits. The result of reckoning an estimation of the value the zoo Surabaya through economic approach travel cost method as much as Rp 33.348.713.604,00 in one year.